Coverage of Science, Technology, and Innovation by Major Broadcast Networks in Nigeria: an Exploratory Survey - Obot, Charles; Batta, Herbert; Nda, Iniobong; Ekeanyanwu, Nnamdi (European Scientific Journal, ESJ, 2022)
This investigates the nature of reportage accorded Science, Technology, and Innovation (STI) matters by the African Independent Television (AIT), Federal Radio Corporation of Nigeria (FRCN) and Nigerian Television Authority (NTA). Science communication research is only beginning to feature in Nigeria as a key aspect of academic inquiry. However, science and technology broadcast has been going on for decades. The study aims at knowing the feedback those broadcast media houses have been receiving from the public about the dissemination of emerging science, technology, and innovation matters as well as the perception by the select broadcast houses of the contributions of Nigeriaâ€™s science community to specific areas of national development. The study adopts interviews as the instrument of data collection from senior correspondents directly involved with the selected broadcast houses’ coverage and reportage of science, technology, and innovation. The major findings of the research are that not all the broadcast houses have science desks and science correspondents, although all the media houses under study cover STI matters; though in varying degrees and only the NTA has a science correspondent who is a science graduate. Also, the FRCN and NTA provide extensive coverage of STI matters with dedicated programs and segments for STI on their stations and correspondents covering major STI Agencies and the Ministry of Science and Technology Headquarters. It is recommended that broadcast media in the country should show greater commitment to the coverage of STI matters since the majority of audience members depend on the broadcast media for information on all aspects of life. Moreover, a content analysis of news bulletins of the selected broadcast houses and other news media should be conducted to have more data on the coverage of STI matter.